Assessment of Prevalence of Iron Deficiency Anemia among Known Population (Academia Journal of Medicine, 2018)
Background: The most significant and common cause of anemia is iron deficiency. Hence, we planned the present study to assess the  prevalence of iron deficiency anemia among known population. Subjects and Methods: A total of 350 subjects who reported to the  department of internal medicine for routine checkup were included in the present study.Blood samples were obtained from all the subjects and  were sent to central laboratory for the assessment of blood hemoglobin levels. Criteria described in the past literature were used for  categorizing patients with iron deficiency anemia. Females with mean hemoglobin concentration less than 11.5 g/dL, and males with mean  hemoglobin concentrations less than14 g/dL were categorized as anemic.6 All the results were analyzed by SPSS software. Results: Overall  prevalence of iron deficiency anemia in the present study was 15.28 percent. The overall prevalence of iron deficiency anemia was found to be  higher among subjects with more than 60 years of age. Also, significantly higher prevalence of iron deficiency anemia was found among  females. Conclusion: Prevalence of iron deficiency anemia was found to be higher among females and illiterates. Therefore health education  programs are recommended in future for increasing the awareness of adverse events associated with iron deficiency anemia among general  population.
Keywords: Iron deficiency anemia; Prevalence